The effect of organizational learning culture on the organizational commitment: A case study of Majlis Amanah Rakyat (MARA) Terengganu / Sarah Syuhaidah Mohd - Mohd, Sarah Syuhaidah (Bachelor of Science (Hons) Statistics, 2015)
Organizational commitment becomes crucial in every organization and has been studied in the public, private, and non-profit sector, and more recently internationally. Organizational commitment has three main domain components. There are continuous learning, team learning and strategic leadership. A crosssectional study was carried out to examine factors influencing the organizational commitment among staff at Majlis Amanah Rakyat (MARA) Negeri Terengganu. From this study, continuous learning and team learning influence organizational commitment towards their organization. Questionnaire contain of four (5) sections which are demographic characteristic, continuous learning, team learning, strategic leadership and organizational commitment. Descriptive analysis, t-test, correlation and multiple linear regressions were used to analyze the data. Correlation analysis showed a significant association between continuous learning, team learning and strategic leadership with of organizational commitment. However, all component continuous learning, team learning and strategic leadership with of organizational commitment showed a significant correlation with organizational commitment. On further analysis using multiple linear regression it was found that only continuous and team learning gave significant value (p<0.05). As the conclusion, findings from this study suggested that continuous and team learning of the staff being studied does contribute to their organizational commitment